Modeling of working environment and coverage path planning method of combine harvesters - Lu, En; Xu, Lizhang; Li, Yaoming; Tang, Zhong; Ma, Zheng (International Journal of Agricultural and Biological Engineering, 2020)
This paper mainly studied the working environment modeling and coverage path planning of combine harvesters. The boundaries of the farmland to be harvested were extracted through the farmland satellite imagery and canny algorithm. The polygon approximation method was used to fit the extracted boundaries as polygons. The edge offset of the farmland and obstacles was realized based on the principle of straight skeleton. According to the structure data of the split points which were obtained through the improved scan line algorithm, the coverage path planning of the combine harvester was realized. Moreover, the circular arc transition algorithm was used to optimize the harvesting paths to achieve the smooth turning of the combine harvester at the edge of farmland and when encountering obstacles. The simulation results show that the proposed the proposed polygon approximation method can accurately depict the boundaries of the farmland to be harvested, and reduce the amount of data to be stored. Additionally, the designed path planning method can realize the coverage path planning of the combine harvester in irregular and internal obstacle farmland.Keywords: combine harvester, environmental modeling, path planning, farmland turningDOI: 10.25165/j.ijabe.20201302.5210Citation: Lu E, Xu L Z, Li Y M, Tang Z, Ma Z. Modeling of working environment and coverage path planning method of combine harvesters. Int J Agric & Biol Eng, 2020; 13(2): 132–137.